Appraisal Analysis on The Album Midnights: Graduation System Analysis - Muhammad Fiqri Assidiqi SP; Setyo Prasiyanto Cahyono (Universitas Muhammadiyah Semarang, 2023)
Appraisal appears to be interpersonal meaning system in systemic functional linguistics (Halliday 1994). Appraisal negotiates the social relationship by expressing to the reader or the listener how the one who expresses about people or things. A song must contain a story or meaning behind the lyrics. This study explores the use of amplifications, namely graduation, in lyrics of 5 selected songs by Taylor Swift. The data were taken from the best-selling album of 2022, Midnights, by the American singer-songwriter. The songs discussed in this research were: Anti-Hero, Lavender Haze, Karma, Mastermind, and Midnight Rain. The reasons researchers chose the sampling songs are: (1) the collected data consisting all of the graduation systems, (2) the album is known as the record-breaker in any music category. The type of the research is descriptive qualitative method. The method of the data collection is the researchers listened to the selected songs on the singer’s YouTube channel and then got the transcript lyrics on Genius website. The technique of the data analysis of this study employed the appraisal system by Martin and Rose’s framework 2007. This research aims to discover the categories in the graduation system, force and focus, in the five selected songs from the album midnights. Force and focus still can be classified deeper. In force there are: (1) attitudinal lexis, (2) intensifiers, (3) metaphors, and (4) swearing. Meanwhile Focus consists of sharpen and soften. The finding shows that force happens to be used more often than focus. The observed data found out there are 72 graduation systems from 60 lines. The data mostly contains focus subsystem, metaphors with 32 lines (44,4%). The least graduation subsystem that is used in the data is Sharpen Focus with only 3 lines (4,2%).